(3JNQjL GdOdGdGJ GdSeYjI Ydi eG cGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFY hGdYeGdGJ GdTQYjIs - (3CHh GdMSf Ydj Hf eMeO Hf CMeO Hf ehSi Hf eSYhO Hf CHi ZaQI GdNRGYi GHf Pi GdhRGQJjfs; (3GHf XgjQI , eMeO Hf eMeO Hf CHj HcQ Hf Ydj Gdecj GdeNRhej, LeGd GdOjf,J (B986 (3g` s ((3eMeO dHjH s)
(3ChdgG (B:s
(3ef GdHGH GdKGef YTQ , bhdg (B: (3ai GdQLd jQcH Njd GdEeGe jSGHb HgG , hajg KdGKI aUhd GdaUd GdChd ai Cfg Udi Gddg Ydjg hSde cGf jSGHb Hjf GdNjd Qhi GdHNGQi s
(3BNQgG (B:s
(3hef SGFQ GdcJH GdCYeGd GdSdWGfjI ai GdOhd GdCfOdSjI dCHi GdMSf Ydi Hf NjQI GdSMhQi GdejhQbi hGdJMaI GdaGQSjI hcJGH GdcaGjI hGdZfGA ai CMcGe GdZfGA JCdja eMeO Hf YeQ Hf eMeO GdSHJi GdeYQha HGdOQGL hHJeGeg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI GdSGHbI faSgGs
(3hgh GdLRA GdCNjQs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs